INCREASING EFFICIENCY OF INTERACTION BETWEEN THE OBJECT AND SURROUNDING TARGETS USING POSITIONING METHODOLOGY - Spitzer, A. S.; Mashchak, A. V.; Tkachuk, T. I.; Kulyk, I. V. (Systems and Technologies, 2019)
In this article the idea of the theoretical model of the object (O) positioning in space is discussed. The space object positioning takes place on the basis of the enemy targets (ET) and friendly targets (FT) locations. The effective location criterion is determined – the maximum number of ET and the minimum number of ET which falls into the damage zone. Also, in the article the analysis of object own safety is carried out. Proposed model expands the criteria for assessing the characteristics of the object in relation to the environment in which the object is located.